The Influence of Work Motivation and Physical Work Environment on the Performance of ASN Teachers at SMAN 1 Sukaresmi - Nur Rostari; Khaerul Rizal Abdurrahman (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The effectiveness of teachers significantly contributes to enhancing educational quality and fulfilling the objectives of academic institutions. The significance of teachers as the primary influence on the instructional and learning experience. Consequently, teachers are anticipated to provide a high standard of performance to facilitate effective learning, character development, and student success. Nonetheless, attaining peak teacher efficacy needs sufficient backing from both personal and organisational elements. At SMAN 1 Sukaresmi, many concerns about teacher efficacy have been noticed, encompassing signs of inadequate work motivation and physical work environmental factors may not entirely facilitate teachers in fulfilling their professional duties. This study aims to investigate the influence of work motivation and the physical work environment on the performance of ASN educators at SMAN 1 Sukaresmi. This research approach utilises a quantitative framework, collecting information via questionnaires, interviews, and documentation from all ASN educators at SMAN 1 Sukaresmi as subjects. The collected data was analysed by multiple linear regression utilizing SPSS version 27. Hypothesis testing was performed utilizing partial tests, simultaneous tests, and the measurement of the determination coefficient (R²) to evaluate the influence of independent variables on teacher performance, applying quantitative descriptive and quantitative associative analytic methodologies. The study outcomes demonstrate work motivation has a beneficial effect on the performance of ASN teachers at SMAN 1 Sukaresmi, and the physical work environment similarly enhances their performance. Furthermore, both job motivation and the physical work environment simultaneously affect the performance of ASN instructors at SMAN 1 Sukaresmi. The outcomes suggest improved teacher motivation, supported by a favourable, safe, and adequate physical work environment, might outcome in increased teacher performance. The outcomes of this study highlight the need of improving motivational factors and modernising workplace facilities to enhance the effectiveness of educational endeavours. As a outcome, educational institutions must continue to improve teachers' job motivation and the physical conditions of their work environment to achieve higher levels of teacher performance and educational quality.